Translating the Translator: Identity and Revision in Trungpa Rinpoche’s Buddhism(s) - Galván-Álvarez, Enrique (IAFOR Journal of Literature & Librarianship, 2024)
By exploring how the literal and metaphorical aspects of the teaching/translating activities of Chögyam Trungpa overlap and feed into each other this paper analyses a highly original process of re-inventing tradition against various forms of criticism and censorship, both in the target and the source cultures. This analysis will be articulated along three axes, which correspond to the three Buddhist roles Trungpa was meant to have played: guru (teacher), siddha (accomplished practitioner) and tertön (treasure revealer). The three roles are all concerned with different processes of mediation and, thus, can be thought of as metaphorical translations. Looking at linguistic and cultural translation in terms of those three traditional categories can provide us with a meaningful framework for understanding how Vajrayana Buddhism, and particularly the Tibetan Vajrayana tradition, imagines and conceptualises translation.
Keywords: Tibetan Buddhism; translation; counterculture; Crazy Wisdom; terma; tibetan exile